Electron Spin Waves in Nonmagnetic Conductors with Resonance States of Electrons - Ermolaev, Alexander Mikhailovich; Ulyanov, Nikolai Vladimirovich; Eрмолаєв, Олександр Михайлович; Ульянов, Микола Володимирович (Kharkiv : Karazin Kharkiv National University, 2008)
Results of theoretical investigation of properties of spin waves in nonmagnetic conductors and heterostructures with 2D electron gas in presence of impurity atoms be able to localize electrons are listed in monograph.

B монографії наведені pезультати теоретичного дослідження властивостей спінових хвиль у немагнітних провідниках та гетероструктурах з двовимірним електронним газом за наявності домішкових атомів, здатних локалізувати електрони.
Keywords: NATURAL SCIENCES::Physics; tenzor; dynamic spin; Kubo formula; Green function; magnetic scattering; quasi-local electron states